IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 11 TAHUN 2000 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KECAMATAN SEMARANG TIMUR - HABIB MUHAMMAD NAJIB; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2018)
This study aims to describe; 1) the implementation of Local Regulation of City of Semarang Number 11 Year 2000 concerning Arrangement and Guidance of PKL in Sub-district of East Semarang; and 2) factors inhibiting the implementation of Local Regulation of City of Semarang Number 11 Year 2000 regarding the Management and Development of street vendors in East Semarang Subdistrict. The research approach used in this research is descriptive research that aims to describe certain social phenomena as well as compare the phenomena that have been determined, so it can be concluded. This type of qualitative research is descriptive because the research does not use much numerical data, it leads to what actually happens on the field, in which the researcher has to see, find and describe what really happened by reviewing the researcher's mind in accordance with the data and facts found. In this case, the researcher uses several informants as informants, which represents the apparatus / government, street vendors and the community. The result of the research shows that the implementation of Regional Regulation Number 11 Year 2000 regarding the Management and Development of PKL in East Semarang Sub-district is not yet optimal. The lack of optimal implementation is motivated by several problems such as the lack of solid socialization, low awareness of the target group to obey the rules, the low supervision of the officers, the number of street vendors that have not been recorded, as well as the low level of PKL education, the competence of human resources namely the executing officers, which is less supportive, as well as internal and external factors of Regional Regulation No. 11 of 2000. Problems that often occur for example they do not want to pack the ground after selling, or littering, which effect the aesthetic city becomes less beautiful and beautiful. Though people would also want the city's aesthetic awake. The agency actually wants them not only to sell in crowded places. They are expected to be a new magnet that creates a crowd even though its location is not in the middle of the city.